The Relationship between Quiescent Inflammatory Bowel Disease and Peripheral Polyneuropathy - ULUÇ, KAYIHAN; TANRIDAĞ, TÜLİN (EDITORIAL OFFICE GUT & LIVER, 2011)
Background/Aims: Inflammatory bowel disease is a chronic, recurrent disorder that involves multiple organ systems. Polyneuropathy is the most common neurological manifestation. The aim of the present study was to investigate the relationship between polyneuropathy and inflammatory bowel disease. Methods: The study included 40 patients with inflammatory bowel disease (20 with ulcerative colitis and 20 with Crohn's disease) and 24 healthy controls. The patients had no clinical signs or symptoms of polyneuropathy. Nerve conduction studies were performed using an electroneuromyography apparatus. Results: Mean distal motor latencies, conduction velocities, and F wave minimum latencies of the right median nerve were significantly abnormal in the patient group, compared to the healthy controls (p<0.05). Conclusions: Some electrophysiological alterations were observed in chronic inflammatory bowel disease patients who showed no clinical signs. While investigating extra-intestinal manifestations in inflammatory bowel disease patients, nerve conduction studies must be performed to identify electrophysiological changes and subclinical peripheral polyneuropathy, which can subsequently develop. (Gut Liver 2011;5:57-60)
Keywords: Inflammatory bowel disease; Polyneuropathy; Electroneuromyography; CROHNS-DISEASE; NEUROPATHY